2017
DOI: 10.1371/journal.pone.0179237
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Mycobacterium massiliense strains having recombinant rpoB gene laterally transferred from Mycobacterium abscessus

Abstract: Recent multi locus sequence typing (MLST) and genome based studies indicate that lateral gene transfer (LGT) events in the rpoB gene are prevalent between Mycobacterium abscessus complex strains. To check the prevalence of the M. massiliense strains subject to rpoB LGT (Rec-mas), we applied rpoB typing (711 bp) to 106 Korean strains of M. massiliense infection that had already been identified by hsp65 sequence analysis (603 bp). The analysis indicated 6 smooth strains in M. massiliense Type I (10.0%, 6/60) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(63 reference statements)
2
10
0
Order By: Relevance
“…Analysis of these results for K. pneumoniae led to the proposal of a hybrid clone, where 80% of the genome originated from a strain similar to ST11 and 20% from ST442 (Chen, Mathema, Pitout, DeLeo, & Kreiswirth, ). In a more recent study on Mycobacterium spp., Kim et al () demonstrated horizontal transfer from Mycobacterium abscessus to Mycobacterium masiliense through sequencing of the rpo B gene . These prior reports evidence the occurrence of recombination events and chromosomic region replacements in bacteria that are non‐pathogenic to fish, with noted pathogenic clone success (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of these results for K. pneumoniae led to the proposal of a hybrid clone, where 80% of the genome originated from a strain similar to ST11 and 20% from ST442 (Chen, Mathema, Pitout, DeLeo, & Kreiswirth, ). In a more recent study on Mycobacterium spp., Kim et al () demonstrated horizontal transfer from Mycobacterium abscessus to Mycobacterium masiliense through sequencing of the rpo B gene . These prior reports evidence the occurrence of recombination events and chromosomic region replacements in bacteria that are non‐pathogenic to fish, with noted pathogenic clone success (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study on Mycobacterium spp., Kim et al () demonstrated horizontal transfer from Mycobacterium abscessus to Mycobacterium masiliense through sequencing of the rpo B gene . These prior reports evidence the occurrence of recombination events and chromosomic region replacements in bacteria that are non‐pathogenic to fish, with noted pathogenic clone success (Kim et al, ). Chilean P. salmonis isolates can already be classified into two genetic groups (LF‐89 T and EM‐90) that present genetic heterogeneity, particularly in regard to pathogenicity and antibiotic resistance, among other phenotypic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic exchanges in the rpoB gene between closely related subspecies within the M. abscessus complex were recently reported to frequently occur ( Macheras et al, 2011 ; Kim et al, 2017 ). In terms of clinical diagnostics, the rpoB typing method lacks power, culminating in 20% failure rates in the M. massiliense subspecies ( Sapriel et al, 2016 ) and thus suggesting they have hybrid rpoB genes, a part of which were from M. abscessus subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…abscessus subsp. abscessus [22], suggesting the potential for misidentification when the rpoB tying method is used to the differentiate among M . abscessus strains.…”
Section: Introductionmentioning
confidence: 99%